THE IMPLEMENTATION OF COOPERATIVE LEARNING METHOD IN TEACHING READING COMPREHENSION - Hadyan, Rifki (2013)
This paper investigated the use of cooperative learning methods in improving students' reading comprehension. the research was conducted to find out whether or not cooperative learning methods improve students' reading comprehension, and to find out students' responses toward the implementation of cooperative learning methods. the research design employed in this research was classroom action research which consisted of four main steps: planning, acting, observing, and reflecting (kemmis and mc taggart, 1988) which conducted in two cycles. the study was conducted at xi grade of culinary class which involve thirty one students. observation checklists, students' questionnaire, evaluation sheet and students' reading score were implemented as instruments to collect the data. the findings of the study showed that cooperative learning methods (stad and jigsaw) improve the students' reading comprehension in descriptive text. on the first cycle, there were 13 students (42%) who passed the reading posttest, while in cycle 2, the students who passed the reading posttest were 25 students (86%). the studentswere considered pass the tests when theyreach minimum mastering criteria (mmc). the findings also showed that the students gave positive responses since they stated that cooperative learning methods were fun and helped them in understanding descriptive text and they wanted to know more about cooperative learning methods. keywords : cooperative learning, reading, descriptive text.